PEMBELAJARAN BAHASA INGGRIS BERDASARKAN PENDEKATAN SAINTIFIK KURIKULUM 2013 DI KELAS VII MTS DDI JOLLE - Kasmah Kasmah; Syamsir Bin Rukka (Pascasarjana IAIN Sorong, 2018)
>This research was aimed at investigating (1) lesson plan based on scientific approach as curriculum 2013 in the class VII of MTs Negeri DDI Jolle; (2) the implementation of English learning based on saintific approach; (3) the model of the learning in the curriculum 2013; (4) the use of instructional media; and (5) the assessment process based on curriculum 2013. This research was qualitative descriptive. Data were collected by using documentation, observation, and interview. The results showed that (1) lesson plan used in english learning in the class VII of MTs DDI Jolle accordance to Ministry Rule (Permen) No. 58, 2014; (2) the learning process has reflected the achievement of KI-1, KI-2, KI-3, and KI-4; (3) English learning based on a scientific approach covering five learning experience of observing, questioning, experimenting, associating and communicating feasible although it still not optimal; (4) the use of instructional media is not maximized because infocus display less clear and not attractive; (5) the assessment consist of attitude, knowledge, and skill. Based on this research suggested to the teachers to familiarize themselves communicating in English. Principals should consider the availability of instructional media. Other researchers are advised to conduct research related to the assessment process in curriculum 2013